The impact of utilizing oyster shell soil conditioner on the growth of tomato plants and the composition of inter-root soil bacterial communities in an acidic soil environment - Zheng, Yi; Yu, Chaofan; Xiao, Yujun; Ye, Tinge; Wang, Songgang (Frontiers in Microbiology, 2024)
In this study, the effects of oyster shell soil conditioner on tomato growth in acidic soil were investigated, and the species and structure of soil bacterial populations near tomato roots were analyzed. The experiment set up a control group and two oyster shell soil conditioning agents, OS and OSF, in the treatment group. The results showed that oyster shell soil conditioner could change the physical and chemical properties of soil and increase the total nitrogen, total carbon, pH value, and electrical conductivity of soil. At the same time, promote the germination of tomato seeds and seedling growth. The diversity of the bacterial population decreased slightly, but the abundance of beneficial bacteria increased, which improved the resistance of tomato plants to related diseases.